A phosphatidylinositol 3-kinase-Pax3 axis regulates Brn-2 expression in melanoma. - Bonvin, E; Falletta, P; Shaw, H; Delmas, V; Goding, C (2012)
Deregulation of transcription arising from mutations in key signaling pathways is a hallmark of cancer. In melanoma, the most aggressive and lethal form of skin cancer, the Brn-2 transcription factor (POU3F2) regulates proliferation and invasiveness and lies downstream from mitogen-activated protein kinase (MAPK) and Wnt/β-catenin, two melanoma-associated signaling pathways. In vivo Brn-2 represses expression of the microphthalmia-associated transcription factor, MITF, to drive cells to a more stem cell-like and invasive phenotype. Given the key role of Brn-2 in regulating melanoma biology, understanding the signaling pathways that drive Brn-2 expression is an important issue. Here, we show that inhibition of phosphatidylinositol 3-kinase (PI3K) signaling reduces invasiveness of melanoma cells in culture and strongly inhibits Brn-2 expression. Pax3, a transcription factor regulating melanocyte lineage-specific genes, directly binds and regulates the Brn-2 promoter, and Pax3 expression is also decreased upon PI3K inhibition. Collectively, our results highlight a crucial role for PI3K in regulating Brn-2 and Pax3 expression, reveal a mechanism by which PI3K can regulate invasiveness, and imply that PI3K signaling is a key determinant of melanoma subpopulation diversity. Together with our previous work, the results presented here now place Brn-2 downstream of three melanoma-associated signaling pathways.